2010
DOI: 10.1074/jbc.m110.104786
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Mitochondrial Twin Cx9C Protein Cmc2 Is a Cmc1 Homologue Essential for Cytochrome c Oxidase Biogenesis

Abstract: Mitochondrial copper metabolism and delivery to cytochrome c oxidase and mitochondrially localized CuZn-superoxide dismutase (Sod1) requires a growing number of intermembrane space proteins containing a twin Cx 9 C motif. Among them, Cmc1 was recently identified by our group. Here we describe another conserved mitochondrial metallochaperonelike protein, Cmc2, a close homologue of Cmc1, whose function affects both cytochrome c oxidase and Sod1. In the yeast Saccharomyces cerevisiae, Cmc2 localizes to the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Although the precise mechanisms for these pleiotropic effects remain to be explored, they were similar to the alterations measured in a ⌬cox14 strain (Fig. 2D) and several other COX assembly mutants (29).…”
Section: Resultsmentioning
confidence: 61%
“…Although the precise mechanisms for these pleiotropic effects remain to be explored, they were similar to the alterations measured in a ⌬cox14 strain (Fig. 2D) and several other COX assembly mutants (29).…”
Section: Resultsmentioning
confidence: 61%
“…Two strains that showed a strong respiratory growth stimulation by GSH and DTT caught our attention because they lacked genes for the ''twin Cx 9 C'' proteins Cmc1 and Coa4, which were shown before to play a role in the biogenesis of cytochrome c oxidase (7,22,23,32). These strains showed no (Dcmc1) or poor (Dcoa4) growth on glycerol but were strongly stimulated by either GSH or DTT.…”
Section: Reductants Suppress the Growth Defect Of Mutants Lacking Cmcmentioning
confidence: 99%
“…It was previously demonstrated that Cmc1 and Coa4 play a direct or indirect role in the assembly of cytochrome c oxidase (7,22,23). We therefore analyzed the activity of cytochrome c oxidase in Dcmc1 and Dcoa4 mitochondria (Fig.…”
Section: Mutants Lacking Cmc1 or Coa4 Show Reduced Levels Of Cytochromentioning
confidence: 99%
“…Cox19 and Cox23, which are structurally related to Cox17, are also involved in copper delivery, although they may not bind copper directly (72,73). Likewise, the proteins Cmc1 and Cmc2 have recently been shown to be involved in the maturation of cytochrome c oxidase (74,75).…”
Section: Substrates Of Mitochondrial Disulfide Relaymentioning
confidence: 99%